The effect of pre-weld rolling on distortion and residual stress in fusion welded steel plate - Coules, Harry E.; Cozzolino, Luis D.; Colegrove, Paul A.; Wen, S. (Transtec Publications; 1999, 2011)
Local rolling and other mechanical tensioning techniques can be highly effective at reducing residual stress and distortion in thin plate welds prone to buckling. However, the issues of high capital cost and low scalability currently prevent wider adoption of such processes. Pre-weld rolling aims to address these issues and can be applied easily to each component prior to fabrication. The results of an initial trial are presented, and indicate that post-weld distortion can be reduced by an average of 38% when correct rolling parameters are used. Finally, the mechanism by which prerolling acts to modify the state of residual stress around a weld line is discussed.